Rapid increase in Omicron infections in England during December 2021: REACT-1 study. - Elliott,P; Bodinier,B; Eales,O; Wang,H; Haw,D; Elliott,J; Whitaker,M; Jonnerby,J; Tang,D; Walters,CE; Atchison,C; Diggle,PJ; et al. (Science, 2022)
The unprecedented rise in SARS-CoV-2 infections during December 2021 was concurrent with rapid spread of the Omicron variant in England and globally. We analyzed prevalence of SARS-CoV-2 and its dynamics in England from end November to mid-December 2021 among almost 100,000 participants from the REACT-1 study. Prevalence was high with rapid growth nationally and particularly in London during December 2021, and an increasing proportion of infections due to Omicron. We observed large falls in swab positivity among mostly vaccinated older children (12-17 years) compared with unvaccinated younger children (5-11 years), and in adults who received a third (booster) vaccine dose vs. two doses. Our results reinforce the importance of vaccination and booster campaigns, although additional measures have been needed to control the rapid growth of the Omicron variant.